High efficiency dye-sensitized solar cells with a novel two dimensional Cd-V-LDH photoanode - Bendary, Samar H.; Hashem, Amira A.; Mahmoud, Sawsan A. (Frontiers in Materials, 2023)
The present study demonstrates a novel photoanode layer double hydroxide (LDH) for dye-sensitized solar cells (DSSCs). The search for a photoanode (PA) with low cost and high power conversion efficiency (PCE) has become one of the most significant challenges facing researchers. LDH has proven successful as a photocatalyst in various fields. In this paper, a novel Cd-V-LDH with a molar ratio of Cd:V = 1:1 was synthesized by the coprecipitation method and used as a novel PA in DSSCS. X-ray diffraction (XRD), Raman spectroscopy, Scanning electron microscopy (SEM), Fourier Transform infrared spectroscopy (FTIR), Nitrogen sorption analysis, UV–Vis absorption spectrum, Electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) were used to examine the produced Cd-V-LDH. Cd-V-LDH as PA, Eosin Y (EY) as a photosensitizer, LiI-I2 as a liquid electrolyte, and g-C3N4 (GN) as a photocathode (PC) are the component of DSSCs. The series cells of DSSCs were assembled and the available variables have been studied to achieve the best performance under normal conditions. These variables, e.g., concentration and pH of EY, active area of PA, and different types of PC, e.g., graphene oxide (GO), commercial carbon (CC), and (GN). The open circuit voltage (VOC) and short circuit current density (JSC) for the Cd-V-LDH/EY/LiI-I2/GN system were observed to be 705 mV and 12.40 mA/cm2, and has a PCE of 5.4% comparable to Cd-V-LDH/EY/LiI-I2/GO and Cd-V-LDH/EY/LiI-I2/CC, which have PCEs of 4.9% and 3.8%, respectively, in the identical testing conditions.